2022
DOI: 10.1039/d1ta10988j
|View full text |Cite
|
Sign up to set email alerts
|

Non-metallic copolymer material-based universal bio-abiotic hybrid platform for boosting the efficient electronic collection of microbial fuel cells

Abstract: Microbial fuel cell collects the electrons derived from bacterial metabolism, which gradually show potential uses in aerospace and other fields. The major limitation of MFC research lies in the interaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…5 Despite the marked improvements that have been achieved over the past decades, MFCs are still limited by their relatively lower power density that results from sluggish extracellular electron transfer (EET) between the biolms and anodes and weak biolm adhesion. 6,7 The anode materials used as the medium for electron transfer and the support for biolm attachment are considered key structural parts of MFCs. Generally, the MFC performance is improved if the anode materials possess a high specic surface area, porous structure, good electrical conductivity, and remarkable electrocatalytic activity toward the redox reactions in the biolm.…”
Section: Introductionmentioning
confidence: 99%
“…5 Despite the marked improvements that have been achieved over the past decades, MFCs are still limited by their relatively lower power density that results from sluggish extracellular electron transfer (EET) between the biolms and anodes and weak biolm adhesion. 6,7 The anode materials used as the medium for electron transfer and the support for biolm attachment are considered key structural parts of MFCs. Generally, the MFC performance is improved if the anode materials possess a high specic surface area, porous structure, good electrical conductivity, and remarkable electrocatalytic activity toward the redox reactions in the biolm.…”
Section: Introductionmentioning
confidence: 99%
“…Such microbes are named exoelectrogens. [6][7][8] Most of the researchers focus on engineering the MFC architecture 5,9,10 and materials to improve MFC output, 1,9,11,12 which is still insufficient to meet the local power needs. It is reported that power generated by MFCs is several orders of magnitude lower when compared to other conventional energy conversion technologies.…”
Section: Introductionmentioning
confidence: 99%